Generation of series of electron acoustic solitary wave pulses in plasma - Kakad, Amar; Kakad, Bharati (My University, 2019)
One-dimensional fluid simulation is used to investigate the generation of electron-acoustic solitary waves (EASWs) in three-species plasma. We consider an unmagnetized collisionless plasma consisting of cold electrons, hot electrons, and ions. The Gaussian perturbations in the equilibrium electron and ion densities are used to excite the waves in the plasma. This simulation demonstrates the generation of a series of EASW pulses in this three-species plasma through the process of wave breaking. We investigate the behavior of the ponderomotive potential, frequency, and force associated with electrons and ions during the process of the wave breaking. We observed that the ponderomotive potential of the hot electron, which is the driving species for the electron acoustic waves, peaks at the time of wave breaking. The variation of the maximum ponderomotive force acting spatially on the leading and trailing edges of the hump in the cold and hot electron and ion fluid densities shows the maximum imbalance in the magnitude of the ponderomotive force acting on both sides of the hot electron density hump at the time of wave breaking. This reveals that the imbalanced ponderomotive force acting on the hot electron fluid is responsible for the breaking of the electron acoustic wave in plasma. Furthermore, it is observed that the wave breaking process occurs at an earlier time if the hot electron temperature is increased.
Keywords: Ponderomotive force; Electrosatitic structures; Plasma waves